E-ASESMEN UNTUK UJIAN AKHIR (STUDI KASUS: DEPARTEMEN MATEMATIKA, UNIVERSITAS SAM RATULANGI, MANADO) - Saselah, Florencia Fintje; Pinontoan, Benny; Takaendengan, Mahardika Inra (Faculty of Mathematics and Natural Sciences Sam Ratulangi University, 2024)
The Department of Mathematics is one of the Departments in the Faculty of Mathematics and Natural Sciences at Sam Ratulangi University Manado. In the Department of Mathematics, conventional methods for final exam involve manual paper grading, which is not efficient. During seminar assessments, assessment sheets are collected, and grades are computed using Microsoft Excel during thesis exams. The resultant overall grade is recorded with the grade predicate in the official report. The purpose of this study is the creation of an e-Assessment for final exam which can facilitate the processing of the final exam grades of each student. The method used in this research is the waterfall method. The results of this study show that an e-Assessment has been created that helps improve efficiency in the Department of Mathematics in the process of final exam assessment and each feature that has been made runs according to its function and the results of the tests conducted by lecturers have good results.